A new species of the genus Mantisgebia Sakai, 2006 (Crustacea, Decapoda, Gebiidea, Upogebiidae) from the South China Sea - Liu, Wenliang; Liu, Ruiyu (Zootaxa, 2013)
A new species of the genus Mantisgebia Sakai, 2006, M. multispinosa sp. nov., collected from the South China Sea, is described and illustrated. It is readily distinguished from the other three species of the genus by the numerous spines on the cervical groove, hepatic region, and lower margins of the antennular and antennal peduncles.